2008
DOI: 10.1080/02702710701568397
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers' Metaphors of Teaching and Literacy

Abstract: Abstract:The purpose of this study was to examine pre-service elementary teachers' metaphors of teaching and literacy and then relate their metaphorical images of literacy to content presented in the reading methods course. Specifically, fifty-two participants generated responses to open-ended statements, "Teaching is. . ." and "Literacy is. . ." Results indicated that the pre-service teachers' metaphors could be grouped into eleven themes for teaching and fourteen themes for literacy. Two themes of teaching t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 30 publications
1
30
0
12
Order By: Relevance
“…According to Shaw and Mahlios (2008), the most compelling of the cognitive devices, which were elicited to examine teachers' beliefs, is the metaphor.…”
Section: B the Reason For Choosing Metaphormentioning
confidence: 99%
“…According to Shaw and Mahlios (2008), the most compelling of the cognitive devices, which were elicited to examine teachers' beliefs, is the metaphor.…”
Section: B the Reason For Choosing Metaphormentioning
confidence: 99%
“…Metaphors are mental constructs (Lakoff & Johnson, 1980) that lie beneath the surface of a person's awareness and serve as a cognitive device for analogical framing and the defining of experience in order to achieve meaning about life (Massengill Shaw & Mahlios, 2008). According to Billot and King (2015), usually a metaphor communicates an idea or feeling about something; however, it is sometimes used when something is difficult to express.…”
Section: Introductionmentioning
confidence: 99%
“…Nikitina and Furuoka (2008), after reviewing studies that employed metaphors to approach the conception of teachers and teaching, observed that certain images (teachers as father/mother and teachers as artists) feature in diverse educational and sociocultural contexts. Likewise, MassenhillShaw and Mahlios (2008) found that upbringing was one of the prevailing categories, as did Lin, Shein and Yang (2012). A study carried out with students in their fifth and eighth year of elementary school determined that, among the students, the most recurrent metaphor for teacher was that of father/mother (Karadag and Gültekin, 2012).…”
Section: Discussionmentioning
confidence: 96%